Drug Related Problems (Drps) Penggunaan Obat Anti Asma Pada Pasien Pediatri Di Klinik ‘X’ - KHAIRANI, NADILA; Yanuarto, Tri; Dharmayanti, Luky (Akademi Farmasi Yarsi Pontianak, 2025)
Asthma is a chronic non-communicable disease, with a high prevalence among children in Indonesia, yet adequate treatment is still low. Unoptimally managed asthma can lead to relapses and reduce patients' quality of life. A crucial aspect of therapy is managing Drug-Related Problems (DRPs) in pediatric patients, who have different physiological characteristics than adults. This study aimed to determine the incidence and categories of DRPs based on the Cipolle classification: requiring additional medication, medication without indication, too high a dose, and too low a dose. This study used a descriptive, observational method with a retrospective approach, utilizing secondary data in the form of medical records of pediatric patients diagnosed with asthma from January to December 2024. Sampling was carried out using purposive sampling with a sample size of 101 patients with inclusion criteria. Data analysis was conducted descriptively to obtain the frequency and percentage of DRPs. The incidence of DRPs in pediatric patients with asthma was quite significant, with the most common DRPs being the need for additional medication, followed by too low a dose, then medication without an indication, and finally, too high a dose. Patient characteristics showed a predominance of male gender (60%), and the largest age group was 3–5 years (29.09%). The most common comorbidities were rhinitis (38.98%) and acute respiratory infections (ARI) (28.81%).